Pennisetum glaucum as a phytoremediator(:) development and ecotoxicological responses to tebuthiuron, thiamethoxam and/or vinasse in soil - Pincerato, Giuliano Mikael Tonelo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The intensive use of persistent pesticides in agriculture poses significant environmental challenges, particularly for soil health and biodiversity. This study integrates findings from three complementary investigations to evaluate the environmental behavior of the insecticide thiamethoxam and the herbicide tebuthiuron, their interactions with vinasse (a byproduct of sugarcane processing), and the phytoremediation potential of Pennisetum glaucum (millet). The first component provides a comprehensive overview of thiamethoxam’s ecotoxicological impact and presents biological strategies for mitigation, including phytoremediation and microbial degradation. The second experimental study demonstrates that the combined application of vinasse and P. glaucum significantly reduces soil ecotoxicity, particularly during the early stages of plant development, as assessed by bioassays using Lactuca sativa. The third study applies machine learning regression models with SHAP interpretation to predict the biometric responses of P. glaucum under different contamination scenarios. Results highlight that plant development time is the most influential variable, while vinasse contributes positively to growth. In contrast, tebuthiuron and thiamethoxam exhibit neutral to negative effects. This interdisciplinary approach, merging environmental toxicology, phytoremediation, and predictive modeling, supports the use of P. glaucum as a sustainable solution for restoring pesticide-contaminated soils, particularly in sugarcane production systems.

O uso intensivo de pesticidas persistentes na agricultura impõe desafios ambientais significativos, especialmente para a saúde do solo e a biodiversidade. Este estudo integra resultados de três investigações complementares para avaliar o comportamento ambiental do inseticida thiamethoxam e do herbicida tebuthiuron, suas interações com a vinhaça (subproduto do processamento da cana-de-açúcar) e o potencial de fitorremediação de Pennisetum glaucum (milheto). O primeiro componente oferece uma visão abrangente do impacto ecotoxicológico do thiamethoxam e apresenta estratégias biológicas para mitigação, incluindo fitorremediação e degradação microbiana. O segundo estudo experimental demonstra que a aplicação combinada de vinhaça e P. glaucum reduz significativamente a ecotoxicidade do solo, especialmente durante as primeiras fases do desenvolvimento vegetal, avaliada por bioensaios com Lactuca sativa. O terceiro estudo utiliza modelos de regressão de aprendizado de máquina com interpretação SHAP para prever as respostas biométricas de P. glaucum em diferentes cenários de contaminação. Os resultados destacam que o tempo de desenvolvimento da planta é a variável mais influente, enquanto a vinhaça contribui positivamente para o crescimento. Em contraste, tebuthiuron e thiamethoxam apresentam efeitos neutros a negativos. Esta abordagem interdisciplinar, que combina toxicologia ambiental, fitorremediação e modelagem preditiva, reforça o uso de P. glaucum como uma solução sustentável para a recuperação de solos contaminados por pesticidas, especialmente em sistemas de produção de cana-de-açúcar.
Pennisetum glaucum como fitoremediador(:) desenvolvimento e respostas ecotoxicológicas ao tebuthiuron, thiamethoxam e/ou vinhaça no solo
Keywords: Machine learning; Phytoremediation; SHAP; Soil ecotoxicity; Thiamethoxam; Tebuthiuron; Vinasse; Aprendizado de máquina; Fitorremediação; Ecotoxicidade do solo; Vinhaça